2022
DOI: 10.1093/geronb/gbac126
|View full text |Cite
|
Sign up to set email alerts
|

Surviving Through Solitude: A Prospective National Study of the Impact of the Early COVID-19 Pandemic and a Visiting Ban on Loneliness Among Nursing Home Residents in Sweden

Abstract: Objectives Targeted social distancing measures were widely implemented for nursing home residents when the extremely high COVID-19 mortality in this setting became apparent. Still, there is still scarce rigorous research examining how the pandemic and accompanying social distancing measures impacted loneliness in this group. This prospective nation-wide Swedish study of nursing home residents aimed to examine the impact on loneliness of the early phase of the pandemic and of a national visiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…On a population level, we observed similar levels of loneliness before and during the pandemic. This corroborates some findings [3,4] and contradicts others pointing to an increase in loneliness, particularly among those who were most at risk of social isolation and loneliness, including those receiving home care [18,19]. It is noteworthy that in the analysis of region as an explanatory factor in the likelihood of experiencing loneliness in 2021, Finland scored higher.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…On a population level, we observed similar levels of loneliness before and during the pandemic. This corroborates some findings [3,4] and contradicts others pointing to an increase in loneliness, particularly among those who were most at risk of social isolation and loneliness, including those receiving home care [18,19]. It is noteworthy that in the analysis of region as an explanatory factor in the likelihood of experiencing loneliness in 2021, Finland scored higher.…”
Section: Discussionsupporting
confidence: 85%
“…For example, Finland implemented lockdown in the spring of 2020, whereas Sweden remained relatively open and chose to rely more on voluntary adherence to recommendations. The authorities in both countries, however, emphasised the need to protect children, older adults over the age of 70 and the chronically ill. For example, all kinds of leisure activities, including social gatherings, in Swedish nursing homes were banned for older adults [18] and highly restricted for all other older adults, including physical and social distancing [19]. It has been shown that in areas with social isolation and restrictions, an increased sedentary lifestyle was reported among older adults whose level of physical activity decreased [20].…”
Section: Introductionmentioning
confidence: 99%
“…Analyses were performed separately for the 2019 (before the pandemic) and 2020 (during the pandemic) surveys, as well as collapsed for comparison of estimates between the years. Collapsing all observations within each year was chosen as previous studies on the same population have found no specific loneliness impact attributable to the introduction of restrictive policies among either home care recipients ( Gustafsson et al, 2022a ) or nursing home residents ( Gustafsson et al, 2022b ).…”
Section: Methodsmentioning
confidence: 99%
“…Despite this ostensibly vulnerable position of older adults, empirical research has found a surprisingly modest impact on elderly's loneliness during at least the early phase of the pandemic ( Lebrasseur et al, 2021 ; Parlapani et al, 2021 ), including in Sweden ( Gustafsson et al, 2022b ; Kivi et al, 2021 ). These observations have subsequently led to measured discussions about older adults' vulnerability and resilience to the psychosocial impact of the pandemic ( Fristedt et al, 2021 ; Gustafsson et al, 2022b ; Losada-Baltar et al, 2021 ; Parlapani et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation